Service Quality and Customer Commitment Influence on Satisfaction: The Mediating Role of Trust - Sri Endang; Adnan Hakim; Sinarwaty (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to evaluate the influence of service quality and consumer commitment on fishermen's satisfaction with trust as a mediating variable at Samudra Kendari Port. Using a quantitative approach with a survey method, data were obtained from 90 fishermen selected based on the number of research indicators and analyzed with Structural Equation Modeling–Partial Least Square (SEM-PLS). The results of the study show that service quality and consumer commitment have a significant effect on satisfaction, as well as contributing to forming trust as the main mediator. The findings also revealed that the dimensions of reliability, assurance, and empathy are the strongest supports in building trust, while affective and normative commitments also strengthen the psychological relationship between fishermen and ports. Trust has been proven to mediate the influence of service quality and commitment on satisfaction, thereby increasing the effectiveness of long-term relationships between fishermen and port managers. Overall, this study confirms that consistent, professional, and user-oriented services are crucial factors in creating satisfaction and loyalty in the port services sector.